2016
DOI: 10.1111/bph.13438
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate inhibits atrial metabolic remodelling in atrial fibrillation through PPAR‐α/sirtuin 1/PGC‐1α pathway

Abstract: BACKGROUND AND PURPOSEAtrial metabolic remodelling is critical for the process of atrial fibrillation (AF). The PPAR-α/sirtuin 1 /PPAR co-activator α (PGC-1α) pathway plays an important role in maintaining energy metabolism. However, the effect of the PPAR-α agonist fenofibrate on AF is unclear. Therefore, the aim of this study was to determine the effect of fenofibrate on atrial metabolic remodelling in AF and explore its possible mechanisms of action. EXPERIMENTAL APPROACHThe expression of metabolic proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 62 publications
(77 reference statements)
6
58
0
Order By: Relevance
“…Our previous proteomics study showed that VLCAD, the initial rate-limiting enzyme in mitochondrial fatty acid β-oxidation, was decreased in the LAA tissue of permanent AF patients [15]. Previous studies also found decreased expression of CPT-1 in AF model [16]. These are consistent with the findings of our present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our previous proteomics study showed that VLCAD, the initial rate-limiting enzyme in mitochondrial fatty acid β-oxidation, was decreased in the LAA tissue of permanent AF patients [15]. Previous studies also found decreased expression of CPT-1 in AF model [16]. These are consistent with the findings of our present study.…”
Section: Discussionsupporting
confidence: 93%
“…Activation of PPAR-α induces FA uptake and oxidation through upregulating the gene expression of FAT/CD36, CPT-1, VLCAD, etc. Previous studies demonstrated decreased activation of PGC-1α/PPARα pathway in chronic AF [16]. AMPK, which can improve fatty acids metabolism via phosphorylation of PGC-1α, was also found decreased in AF [5].…”
Section: Discussionmentioning
confidence: 74%
“…In addition to oxidative stress, abnormalities in calcium handling, mitochondria DNA damage, and mitochondrial dysfunction readily disrupt cardiac rhythms through depleting energy supply to the ion channels and transporters. An emerging body of evidence implicates disturbances of energy metabolism in the pathogenesis of AF . Recently, Yan et al found that adiponectin, a metabolism‐related protein secreted by adipose tissue that possesses potent cardioprotective effects, attenuated myocardial infarction injury and improved mitochondrial biogenesis by AMP‐activated protein kinase (AMPK)/peroxisome proliferator–activated receptor‐γ coactivator 1α (PGC‐1α) signaling in diabetic hearts.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al demonstrated that the protein expression of mCPT-1 and GLUT4 is decreased in atrial tissues from AF patients compared with sinus-rhythm patients, indicating reduced FA oxidation and glucose transport. 57 The protein expression of sirtuin1, PGC-1α, and PPAR-α was also decreased in AF. AF rabbits showed a similar decrease in these molecules; treatment with a PPAR-α agonist (fenofibrate) restored the expression of mCPT-1 and GLUT4 and the activation of the PPAR-α/sirtuin1/PGC-1α pathway, suppressing AF inducibility.…”
Section: Ppar-α/pgc-1α Pathwaymentioning
confidence: 95%